2003
DOI: 10.1021/ac034109b
|View full text |Cite
|
Sign up to set email alerts
|

Total Protein Determinations by Particle Beam/Hollow Cathode Optical Emission Spectroscopy

Abstract: A novel method for quantitative total protein determinations is presented. Total protein content is determined by particle beam/hollow cathode optical emission spectroscopy (PB/HC-OES) through monitoring of carbon atomic emission. The PB/HC-OES offers such advantages as ease of operation, exclusion of labor-intensive sample pretreatment processes, rapid analysis, high sensitivity, and low detection limit. The method could also be adapted to be integrated to current microfluidics devices. Parametric optimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 50 publications
1
38
1
Order By: Relevance
“…The HC glow discharge design was altered slightly from the one employed in previous works [10][11][12][13][15][16][17][18][19]21,22]. The HC was machined from a bulk copper rod with an inner diameter of 3.5 mm Fig.…”
Section: Hollow Cathode Glow Discharge Sourcementioning
confidence: 99%
See 3 more Smart Citations
“…The HC glow discharge design was altered slightly from the one employed in previous works [10][11][12][13][15][16][17][18][19]21,22]. The HC was machined from a bulk copper rod with an inner diameter of 3.5 mm Fig.…”
Section: Hollow Cathode Glow Discharge Sourcementioning
confidence: 99%
“…At higher HC temperatures (>100°C), thermal volatilization is the major source of atomization. It has been previously shown that vaporization from the HC walls is the primary means of generating gas-phase species in the PB/HC-OES system [16,19]. Optimal HC temperatures have ranged from 200-300°C, with higher temperatures leading to pyrolysis of carbonaceous samples [10,11,16,19,20].…”
Section: Conditions Effecting Analyte Responsementioning
confidence: 99%
See 2 more Smart Citations
“…Jin et al [97] introduced a particle beam/hollow cathode OED (PB/HC-OES) scheme for the analysis of total protein content by monitoring carbon atomic emission. After optimizing the analysis parameters, BSA solutions were determined with LOD reaching 15 ng/mL.…”
Section: Microplasma-optical Emission Detection (Oed)mentioning
confidence: 99%